In-sacco nutritional worth and in-vitro methane production potential of leguminous forages - LAMBA, J S; WADHWA, M; KAUR, K; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2013)
The present study was undertaken to assess the in-vitro methane production potential of multi-cut berseem, lucerne and shaftal at different cuts. The CP and EE content declined, while the cell wall constituents increased linearly with the increase in number of cuts. The in-sacco studies revealed that the degradation rate and effective degradability (ED) of DM was highest (P